Effects of "Essential AD2" Supplement on Blood Acetaldehyde Levels in Individuals Who Have Aldehyde Dehydrogenase (ALDH2) Deficiency. (September 2019) - Fujioka, Ken; Gordon, Spencer
Abstract : Background: It is estimated that 1 billion people in the world have a point mutation in the gene encoding the aldehyde dehydrogenase 2 (ALDH2) enzyme, the primary enzyme responsible for the metabolism of acetaldehyde. The presence of this mutation is called ALDH2 deficiency. Because of limited ability to metabolize acetaldehyde, individuals with ALDH2 deficiency experience elevated levels of blood acetaldehyde after exposure to various common sources such as recreational alcohol. Because of higher levels of acetaldehyde, individuals with ALDH2 deficiency are at higher risk for numerous diseases, including liver cirrhosis, esophageal and gastric cancer, osteoporosis, and Alzheimer disease. Study Question: The present trial was designed to study the effectiveness, safety, and tolerability of a nutritional supplement (Essential AD2). Measures and Outcomes: The primary outcome was change in acetaldehyde levels in the blood after exposure to alcohol in individuals with ALDH2 deficiency before and after the use of study nutritional supplement. Study Design: This was a 28-day open-label trial, comparing initial acetaldehyde levels after alcohol ingestion to levels after 28 days of a nutritional supplement (Essential AD2). The study consisted of 12 subjects genotyped to be heterozygous for the ALDH2 gene mutation. Results and Conclusions: ALDH2 deficient subjects showed a significant decrease in average blood acetaldehyde level 20 minutes after alcohol consumption (from 0.91 mg/dL to 0.71 mg/dL, P value = 0.02) after receiving 28 days of the nutritional supplement. Acetaldehyde levels taken at 10 minutes and 40 minutes also showed a decrease, although they were not statistically significant. In addition, safety tests looking at liver function tests showed a decrease in aspartate transaminase and alanine transaminase liver proteins from 27.3 to 15.2 and 20.9 to 13.2, respectively, over the 28 days. The treatment was well tolerated and no significant side effects were noted.